Effect of neem leaf meal supplementation on growth performance, serum biochemical properties and cholesterol level in meat of broiler chickens - Narayanan, Kaushelia Eluzthassan (2016)
Neem (Azadirachta indica) commonly known as ‘margosa’ provides medicine and nutritive values to broilers. The objective of this study was to determine the effect of neem leaf meal supplementation on the body weight, average feed intake, feed conversion ratio (FCR), dressing percentage, pH and colour of chicken breast meat, cholesterol content in chicken breast meat and serum biochemical properties. A total of 96 one-day-old Cobb-500 broiler chicks were raised until 42 days of age under open house system. The chicks were divided into four groups in a completely randomized design (CRD): T1: Control – Basal diet; T2: Basal diet + 0.3% neem leaf meal; T3: Basal diet + 0.5% neem leaf meal; T4: Basal diet + 1% neem leaf meal. Fresh, green and undamaged mature neem leaves were collected from a number of trees from the same village and grounded to produce neem leaf meal. The birds were fed with commercially prepared starter ration from day 1 to day 21, and the diet was changed to broiler finisher ration on day 22 until slaughter. Feed and water were given to them ad libitium for 6 weeks. At the end of the experiment, all the birds were slaughtered and blood was collected for serum biochemical analysis. Colour, pH and cholesterol assessment were conducted on the breast muscle. Body weight, average feed intake and feed conversion ratio were not influenced by neem leaf. Chicken fed 1% neem leaf meal had the lowest meat pH (P<0.05). Chicken fed 0.5% neem leaf meal showed the highest redness (a*) value (P<0.05). Chicken fed 0.5% neem leaf meal had the highest cholesterol in meat compared with other treatment (P<0.05). However, the level of cholesterol in all treatments was still within the normal range. Neem leaf meal had no effect on dressing percentage, lightness (L*) and yellowness (b*) of breast meat muscle (P>0.05, respectively). Chicken fed 0.5% neem leaf meal had the highest urea, creatinine and ALT (Alanine transaminase) level in blood serum. While, 1% neem leaf meal had the highest AST (Aspartate transaminase) value. It was concluded that neem leaf meal had no effect on the final body weight, average feed intake, feed conversion ratio as well as meat pH and colour. Neem leaf meal increased the cholesterol level in meat and increased biochemical properties involved in the kidney and liver functions. Based on my study, I would not recommend farmers to feed neem leaf meal for broiler chicken.